A study of inactivation of Chlamydia trachomatis by normal human serum. Issue 6 (December 1983) - Johnson, A P; Osborn, M F; Rowntree, S; Thomas, B J; Taylor-Robinson, D
Abstract : To assess the effect of human serum on the viability of Chlamydia trachomatis, organisms were mixed with unheated and heat inactivated homologous serum, and the numbers surviving after incubation at 37 degrees C for 1 hour were compared. With a pool of sera obtained from 12 donors, the number of chlamydiae surviving incubation in unheated serum was less than 1% of that surviving incubation in heat inactivated serum. The antichlamydial activity of the unheated pooled serum samples could be noticeably reduced by treatment with Mg-EGTA (ethyleneglycolbis (beta-amino ethyl ether)-N, N'-tetra-acetic acid). This indicated a requirement for calcium ions and showed that the alternative pathway of complement activation played only a minor role, if any, in the inactivation process. When 12 serum samples were tested individually it was found that four inactivated chlamydiae to an extent comparable with that seen with the pooled serum. The other eight samples showed only moderate (or slight) antichlamydial activity, with survival rates in unheated serum of 20-60% (or more than 60%) of those in heat inactivated serum. There was no correlation between the titres of antichlamydial antibodies and antichlamydial activity, all serum samples having undetectable or low concentrations of antibody on measurement by micro-immunofluorescence. The antichlamydial activity destroyed by heating was restored, however, when heat inactivated serum was mixed with an equal volume of an unheated serum that was not inhibitory to chlamydiae. When the latter serum was heated before addition antichlamydial activity was not restored, indicating the requirement of both a heat stable and a heat labile factor. This observation and the need for calcium ions for inactivation of chlamydiae are compatable with killing mediated by antibody and complement. Thus serum samples from individuals with no clinical or serological evidence of infection with chlamydiae vary in their ability to inactivate the organism, some having antichlamydial activity which is possibly mediated by antibody and complement.